Nicholas Miraculous The Amazing Career of the Redoubtable Dr. Nicholas Murray Butler - Rosenthal, Michael (Columbia University Press, 2015)
To those who loved him, like Teddy Roosevelt, he was "Nicholas Miraculous," the fabled educator who had a hand in everything; to those who did not, like novelist Upton Sinclair, he was "the intellectual leader of the American plutocracy," a champion of "false and cruel ideals." Ezra Pound branded him "one of the more loathsome figures" of the age. Whether celebrated or despised, Nicholas Murray Butler (18621947) was an irresistible force who helped shape American history. With wit and irony, Rosenthal investigates Butler's rise to prominence as president of Columbia University, which he presided over for forty-four years and developed into one of the world's most distinguished centers for research and teaching. During his time as president, Butler won the Nobel Peace Prize and headed the Carnegie Endowment and the American Academy of Arts and Letters, among innumerable other organizations. In 1920, he sought the Republican nomination for president, managing to garner more votes on the first ballot than the eventual winner, Warren Harding. The book's richly detailed, elegantly crafted narrative captures the mania and genius that propelled Butler to extraordinary achievements. Thick with social, cultural, and political history, both American and global, Nicholas Miraculous recreates Butler's prodigious career along with the complexity of the age that nourished him
Description based on publisher supplied metadata and other sources
Keywords: Butler, Nicholas Murray -- 1862-1947; Columbia University; Butler, Nicholas Murray, 1862-1947; College presidents -- United States -- Biography; Columbia University -- Presidents -- Biography; USA; Biografie